STUDENTS’ CHOICES ON TOPICS PUBLISHED IN PROJECT IBUNKA AND THEIR RATIONALES (A CASE STUDY ) - Maolida, Elis Homsini; Mustika, Gilang (Universitas Suryakancana, 2018)
For novice writer, choosing a topic to write can be a difficult stage process since there are many factors to consider. The process of choosing topic and factors contribute to those choices are important to investigate since it can inform the writing teachers and lecturers about possible topics they may bring to the writing class. In addition, the students’ topic choices and their motives provide valuable information for writing teachers and lecturers to understand the students’ writing process, especially pre writing stage, which is very important to consider in teaching writing. This case study reveals students’ choice on topics and their rationales for choosing those topics. Fifteen English department students who took part in an online writing forum for more than twelve weeks, Project Ibunka, were observed and interviewed. The results show that campus activities and friendship were the top two topics chosen by students regarding school life. Meanwhile, entertainment and Events&Spots dominated students’ choice when they were asked to write about cultural topics. On the subject of social theme, majority of students chose educational issues for their topic. Various rationales of students topics choices were also discovered such as students’ interest on the topic, students’ consideration of audience and familiarity on the topic.